An optimal complexity H.264/AVC encoding for video streaming over next generation of wireless multimedia sensor networks. Issue 6 (September 2016) - Ahmed, Adel
Abstract The next generation of sensor node such as Lotus mote enables higher performance, low power consumption, higher storage/memory and higher speed processing capability than the older generation, such as TelosB or MicaZ motes, which facilitates multimedia data pre-processing and compression in wireless multimedia sensor network (WMSN). In WMSNs, multimedia compression is the main issue that performed on a multimedia sensor node because the complexity of multimedia coding can cause a major energy consumption problem. This paper proposes an optimal complexity H.264 encoding for video streaming over next generation of WMSN. It develops the mathematical model for achieving optimal complexity encoding and proposed the most reliable H.264 encoder configuration setting on H.264 coding. The proposed mechanism ensures an optimal encoding complexity, less power consumption and visual quality of the multimedia. The experimental results of this research give an evidence to verify that the proposed mechanism guarantees high QoS performance.